How to Make Sense of Precariousness? Bíos-Precarious and Sensitive Life - Rucovsky, Martin de Mauro (2020)
The operation that we want to emphasize revolves around the problematic area that brings light to the critical work that uses cultural material and assumes a conceptual complementarity between the paths of biopolitics and precariousness. What these analyses and their work with materials clearly indicate is that a set of dimensions, lines of questioning and problematic zones are not given enough relevance in contemporary debates about biopolitics and precariousness. Therefore, there emerges the need to develop a conceptual tool that may account for markers that encode a precarious life. That is, precisely, the common blind spot and, at the same time, the space of conceptual intersection on which we focus: the biopolitical paths that have not been taken into account in the processes of precarization of life and, in equal measure, the theorization about the precarious condition that has not been developed in strictly biopolitical terms. We call this conceptual knot bíos-precarious. This concept stems from the confluence between Judith Butler’s (theoretical) tools in relation to the bodily ontology of precariousness and the intersection between impersonal life and affirmative biopolitics in Roberto Esposito’s biopolitical path.